Molecularly Imprinted Polymer-Nanoporous Carbon Composite-Based Electrochemical Sensor for Selective Detection of Calycosin. Issue 6 (4th April 2019) - Sun, Bolu; Wang, Chaoqun; Cai, Jinying; Li, Dai; Li, Wuyan; Gou, Xiaodan; Gou, Yuqiang; Hu, Fangdi
Abstract : In this study, a newfangled molecularly imprinted electrochemical sensor based on nanoporous carbon (NC) was constructed and applied to the sensitive determination of calycosin in complex Chinese medicine samples. Aniline as functional monomer and calycosin as template were used to assemble molecularly imprinted polymer (MIP), which was bonded to the surface of NC modified glassy carbon electrode (GCE) by electropolymerization. After characterization of the successfully prepared MIP/NC composite, the electrochemical performance of the proposed sensor (MIP/NC/GCE) was evaluated by cyclic voltammetry, electrochemical impedance spectroscopy and chronocoulometry. The results proved that the sensor could accelerate electron transfer rate and heighten specific surface area. Under optimized conditions, the proposed sensor was used to detect calycosin, which displayed good reproducibility, stability and selectivity. The method demonstrated a liner range of 4.20 × 10 −7 ∼1.29 × 10 −4  mol/L with the detection limit of 8.5 × 10 −8  mol/L. Moreover, this study will provide a prospective exploration for the application of electrochemical analysis technology in the active ingredient detection of traditional Chinese medicine.